Occupational Health and Safety Awareness, Knowledge of the Risks and Practices of Risk prevention of Hair and Beauty Salon Workers in Rural and Urban Areas of Western Nepal - Sedhain, Gopal Prasad; Adhikari, Rajendra (Himalayan Journal of Sociology and Anthropology, 2012)
There is a need to meet and maintain high standards of safety, health and hygiene so that no risk is present to workers and clients in salon/parlors. Given the fact that hair and beauty salon workers and customers are at risk, this study is focused on hair and beauty salon workers’ OHS awareness, knowledge of the risks and practices of risk preventions. Based on the data collected by interviewing a total of 60 salon/parlor workers from 60 workplaces in western Nepal, the study has revealed that the level of OHS awareness, knowledge of risk and risk prevention practices among salon/ parlor workers associated with their profession is satisfactory. Similarly, the level of OHS awareness, knowledge of risk and risk prevention practices associated with their profession is more satisfactory in urban area than the rural areas. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7038 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 34-53